Gambaran Proses Rekrutmen, Seleksi dan Penempatan Pegawai di RSUD Pasar Minggu Tahun 2022 - Daeli, David Setiawan; Saputra, Fajar; Ramadhani, Malihah (Health & Medical Sciences, 2024)
Recruitment is an effort to find and influence workers, so they want to apply for job vacancies in the organization/company. The implementation of recruitment and selection is one of the ways that companies do to find and determine prospective employees who will be accepted or rejected by the company. The purpose of the study was to describe the process of recruitment, selection and placement of employees at Pasar Minngu Hospital in 2022. This type of research used a descriptive research method with a qualitative approach. In this study, in-depth interviews were conducted with 2 informants. The method of data collection is by using interview, observation and document review techniques. Based on the results of the study, the process of job analysis stages at Pasar Minggu Hospital in conducting job analysis refers to workload analysis only. The employee recruitment process at Pasar Minggu Hospital still depends on the demand or demands of each unit in need. the employee selection process at Pasar Minggu Hospital starts from the administrative selection stage then to the MMPI test, in the selection process carried out there is still no debriefing process that aims to encourage new employees to get to know the scope of their work well. The placement of employees at Pasar Minggu Hospital is carried out using a method based on the assessment of education, experience and educational certification as well as human resource needs. At Pasar Minggu Hospital, they still have not paid attention to the development of placement criteria which aims to obtain effective and efficient results in the selection and placement recruitment process. Suggestions are expected from the hospital regarding the process of recruitment, selection and placement of employees not depending on the demands or demands of each unit in need